Implementasi Kelas Industri pada Program Keahlian Teknik Kendaraan Ringan Otomotif di SMK Ganesha Tama Boyolali - Tomi Leo Putra Diningrat; Valiant Lukad Perdana Sutrisno (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
Industrial class programs in Vocational High Schools (SMK) are an educational innovation aimed at bridging the gap between the world of education and the requirements of the industry. This study aims to analyze the implementation process of the industrial class program within the Automotive Light Vehicle Engineering Department at SMK Ganesha Tama Boyolali. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and documentation analysis. The data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that the implementation involves five strategic stages: (1) initiating partnership through a Memorandum of Understanding (MoU) with PT Komatsu, (2) adaptive curriculum synchronization to integrate industrial standards, (3) selective student recruitment involving physical and psychological assessments, (4) Teaching Factory (TEFA)-based learning with additional practical hours and the internalization of the 5R/5S work culture, and (5) rigorous discipline monitoring and evaluation. The study concludes that while the program successfully integrates industrial standards into the school environment, the synchronization process remains largely one-way, with the school predominantly adapting to the industry partner's standards.